Neutrophil activation marker CD15+ as a prognostic factor of ocular surface damage in type 2 diabetics - T. M. Zhmud; G.I. Drozhzhyna; L. M. Velychko (Ukrainian Society of Ophthalmologists, 2024)
Purpose: To evaluate the prognostic value of the neutrophil activation marker CD15+ in ocular surface damage in type 2 diabetics. Material and Methods: This study was conducted from January 2021 to January 2021 at the Pirogov Vinnytsia Regional Clinical Hospital, the clinical site of the Medical University. A total of 60 type 2 diabetics (120 eyes) were enrolled, with an average age of 62.1 ± 5.24 years. Results: The prognostic value of the percentage expression of CD15+ in ocular surface damage in type 2 diabetics was for the first time evaluated. A rather high sensitivity of the percentage expression of CD15 (88.3%) allows using it as a parameter for screening for the presence of ocular surface damage in type 2 diabetics. Type 2 diabetics with a percentage of >27% of CD15+ cells had 10.52 times increased odds of ocular surface damage (95%CI, 4.34-25.50; p < 0.0001), and this value of the percentage of CD15+ cells can be used for the purpose of screening for ocular surface damage with a sensitivity of 88.3% (95% СІ, 77.8-94.2) and specificity of 63.3% (95% СІ, 50.7-74.4).